Ring-closing metathesis for the synthesis of heteroaromatics: evaluating routes to pyridines and pyridazines - Donohoe, T; Bower, J; Basutto, J; Fishlock, L; Procopiou, P; Callens, C (2009)
Ring-closing olefin metathesis (RCM) has been applied to the efficient synthesis of densely and diversely substituted pyridine and pyridazine frameworks. Routes to suitable metathesis precursors have been investigated and the scope of the metathesis step has been probed. The metathesis products function as precursors to the target heteroaromatic structures via elimination of a suitable leaving group, which also facilitates earlier steps by serving as a protecting group at nitrogen. Further functionalisation of the metathesis products is possible both prior to and after aromatisation. The net result is a powerful strategy for the de novo synthesis of highly substituted heteroaromatic scaffolds. © 2009 Elsevier Ltd. All rights reserved.